Copper oxide/biopolymer nanocomposites: synthesis and applications, a comprehensive review - Malik, Rajdeep; Ali, Nazreen; Meena, Jagram (Vietnam Journal of Science and Technology, 2024)
Copper oxide particles have a significant role in various fields due to their many properties like special shape, size, and high surface area. Due to their rarity and unique characteristics, such as their large surface area, paramagnetic nature, and ease of separation, Copper oxide nanoparticles have received the greatest attention. Chitosan, Guar Gum, Tamarind, Alginate, starch, cellulose, polysaccharide, etc. are examples of natural biopolymers that have proven to be excellent hosts for the creation of CuO nanoparticles. Long-established fabrication techniques for biopolymer-based CuO nanocomposites include co-precipitations, green synthesis, Solvent Casting Method, Alco thermal method, and Sol-Gel methods. Excellent biological characteristics of Copper oxide/biopolymer nanocomposites include their potent antibacterial activity against a variety of diseases as well as bacteria that are resistant to antibiotics. These characteristics have sparked the creation of numerous strategies with direct biological applications, including customized surfaces with antimicrobial effects, wound dressings, and modified textiles. This study aims to provide the very first biopolymer CuO nanoparticles to be reported in the previous ten years as well as its appealing methodology in diverse applications.